2017
DOI: 10.17860/mersinefd.305762
|View full text |Cite
|
Sign up to set email alerts
|

Uluslararası Öğrenci Değerlendirme Programında Öğrencilerin Matematik Okuryazarlıkları ile Ev ve Okul Eğitim Olanakları Arasındaki İlişkinin Belirlenmesi - (PISA-2012)

Abstract: The purpose of the study is to examine how home (desk, private study room, a quiet place to study, computer, internet connectivity, textbook, and DVD player) and school educational resources (public or private, school location, class size, shortage of mathematics teachers, instructional materials, Internet connection, library materials, buildings and grounds, heating, cooling and lighting) are related to students' mathematical literacy in PISA 2012. The students in Turkey who attended PISA 2012 form the sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
1
0
4
Order By: Relevance
“…One study identified that unsupervised computer use at home had a positive effect on mathematics learning for nine-year-olds (Casey et al, 2012). However, the correlation between home Internet access and mathematics achievement was found to be weak (Acar G€ uvendir, 2017) and negative if the children were younger and from low socio-economic households (Wainer et al, 2015).…”
Section: Mathematicsmentioning
confidence: 99%
“…One study identified that unsupervised computer use at home had a positive effect on mathematics learning for nine-year-olds (Casey et al, 2012). However, the correlation between home Internet access and mathematics achievement was found to be weak (Acar G€ uvendir, 2017) and negative if the children were younger and from low socio-economic households (Wainer et al, 2015).…”
Section: Mathematicsmentioning
confidence: 99%
“…Buna karşın matematiğe ilişkin ilgi, matematikle ilgili davranışlar, öğretmen-öğrenci ilişkisi, derslere devam durumu, matematik kurslarına katılım ve sosyoekonomik değişkenlerin matematik okuryazarlığında anlamlı bir etkiye sahip olmadığı belirlenmiştir. Güvendir (2017), PISA 2012'de öğrencilerin matematik okuryazarlıkları ile ev ve okul eğitim olanakları arasındaki ilişkileri belirlemeye çalışmış, birey düzeyinde bilgisayar sahipliğinin en yüksek ilişkiye sahip ikinci değişken olduğu sonucuna ulaşmıştır. Çalışma sonucunda elde edilen, öğrenci düzeyinde bilgisayar sahipliği değişkeninin okullardaki matematik okuryazarlığı üzerindeki etkisi istatistiksel olarak manidar olması bulgusunun, Güvendir'in (2017) ulaştığı sonuç ile örtüştüğü düşünülmektedir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…nedeniyle olabilir. Bu durum ulusal alanyazındaki bazı çalışmalar tarafından da desteklenmektedir (Güvendir, 2017). Bunun nedeni, ev kaynaklarının öğrenciler tarafından nasıl kullanıldığına bağlı olmaktadır.…”
Section: Tartışma Sonuç Ve öNerilerunclassified